Cyclometallated compounds of intramolecular coordination. - Caires, ACF; Mauro, Antonio Eduardo [UNESP] (Soc Brasileira Quimica, 1996)
This article supplies a review on the chemistry of cyclometallated compounds. Emphasis is given to those formed by cyclometallation reactions. In this class of complexes, called organometallic intramolecular-coordination compounds, a special attention is given to the reactivity of cyclometallated of palladium(II) due to their use in important chemical processes. Metal-carbon bonds in these palladium(II) complexes can undergo a large variety of insertion reactions and they offer a potentially important sequence in organic synthetic methodology,homogeneous catalysis and liquid crystals manufacturing.
Keywords: cyclometallated compounds; cyclometallation reaction; palladium (II) complexes